Dynamics in global DNA methylation and endogenous polyamine levels during protocorm-like bodies induction of Cattleya tigrina A. Richard (Acta Scientiarum. Biological Sciences, 2017)
Cattleya tigrina is endemic to the Atlantic forest biome and classified as vulnerable in the Red Book of Brazilian Flora. In vitro techniques comprise valuable tools for the conservation of endangered plant species. The aim of the present study was to evaluate the morphological features, global DNA methylation levels and free polyamines during protocorm-like bodies (PLBs) induction of C. tigrina. Along with that, an efficient protocol for in vitro propagation of this species is proposed. The first evidences of PLBs induction in C. tigrina occurred at seven days in culture, starting from the basal portion of the leaf abaxial surface. A hypomethylation marked the beginning of cell differentiation, followed by an increased global DNA methylation at 35 days in culture, coinciding with a subtle change in the structures morphogenetic development. During PLBs induction, putrescine exhibited higher levels as compared to spermidine and spermine, and apparently presents a major role during the PLBs induction in C. tigrina. Due to the apparent secondary PLBs formation, this protocol can represent a highly efficient method for in vitro propagation of this species.